Aid Inflows and the Real Effective Exchange Rate in Tanzania - Li, Ying (World Bank, Washington, DC, 2012)
Tanzania is well placed to receive a significant increase in aid inflows in coming years. Despite the potential for the additional aid inflows to raise income levels in the country, increasing them may bring about structural changes in the economy that may be unwelcome. One such change is an appreciation of the real exchange rate that leads to a contraction of traditional export sectors and a loss of export competitiveness. This paper employs a reduced-form equilibrium real exchange rate approach to explain movements in Tanzania's real effective exchange in recent decades. Particular attention is paid to the relationship between aid inflows and the real effective exchange rate. The authors find that the long-run behavior of the real effective exchange rate is influenced by terms of trade movements, the government's trade liberalization efforts, and aid inflows. Positive terms-of-trade movements are associated with an appreciation, periods of improving trade liberalization are associated with a depreciation, and increases in aid inflows are associated with a depreciation in the real effective exchange rate. Although the last result is non-standard, it is not empirically unique and does have theoretical underpinnings. A detailed analysis of this relationship over the last decade shows that the Bank of Tanzania's response to aid inflows is likely the main reason for the finding.